Tara kay nakhan gay - Aneesa saima (Ferozesons; Lahore, 2003)
"Tara Kay Nakhun Gay" by Aneesa Saima is a gripping novel that delves into the life of a strong-willed protagonist, navigating the challenges of love, betrayal, and self-discovery, while questioning societal norms and personal values.